Hiperplasia bilateral de la apófisis coronoides en paciente adolescente. Reporte de caso - Fernández, Gustavo (2024)
Hyperplasia of the coronoid process is a rare alteration that is characterized by the exaggerated and progressive development of said process over periods of months or years, both in height and volume, which finally causes mandibular hypomobility. It is important to highlight the importance of imaging for the correct diagnosis and treatment of said entity, taking into consideration the great variety of differential diagnoses that can occur. In this sense, conventional radiographs constitute a basic and indispensable tool for approaching the diagnosis. However, it is actually the CT scan that offers the greatest precision. The case of a 14-year-old male patient is presented, with no contributing medical history, who was referred for presenting progressive opening limitation since childhood, for which, after clinical and imaging evaluation, he was treated with total bilateral coronoidectomy, postoperative follow-up was performed. for a year in which recurrence of said entity could be observed. This case demonstrates the importance of correct diagnosis, as well as postoperative control and the rehabilitation scheme carried out by the patient.